Progressive Bundling of Fibrillin Microfibrils into Oxytalan Fibers in the Chick Presumptive Dermis. Issue 1 (15th November 2012) - Shinozuka, Keizo; Yamazaki, Yosuke; Yuguchi, Maki; Toriumi, Taku; Suzuki, Rie; Tsuruga, Eichi; Isokawa, Keitaro
Abstract Dorsoventral fibers in the presumptive dermis of the chick limb bud reported first by Hurle's group in 1989 are now revealed as bundles of fibrillin microfibrils (Isokawa et al., 2004). The bundles, which could be called oxytalan fibers at the light microscopic level, are aligned perpendicularly to the overlying ectoderm and form a unique fiber array, originating directly from the basal lamina. This well‐oriented organization is beneficial in examining the process of in vivo bundling of microfibrils into oxytalan fibers. In this study, sections through the presumptive limb dermis were preferentially prepared from chick embryos at Days 4–6 (ED4‐6). Immunohistochemically, fibrillin‐positive dots representing cross‐sectioned surfaces of individual fibers, increased in size from ED4 to 6, but their number per unit area remained constant. Ultrastructurally, a single oxytalan fiber at ED4 consisted of ∼15 microfibrils; the latter number increased fourfold from ED4 to 5 and threefold from ED5 to 6. Oxytalan fibers were all closely associated with mesenchymal cell; notably, the fibers at ED5 and 6 were held in a shallow ditch on the cell body or by lamellipodial cytoplasmic protrusion. In the sites of cell–fiber adhesion, microfibrils in the periphery of an oxytalan fiber appeared to adhere directly or by means of short flocculent strands to a nearby cell membrane; the latter showed a thickening of plasmalemma and its undercoat, indicating the presence of adhesive membrane specification. These findings suggest that the bundling of microfibrils is a progressive and closely cell‐associated process. Anat Rec, 2013. © 2012 Wiley Periodicals, Inc.